2021
DOI: 10.12703/r/10-47
|View full text |Cite
|
Sign up to set email alerts
|

Neurog1, Neurod1, and Atoh1 are essential for spiral ganglia, cochlear nuclei, and cochlear hair cell development

Abstract: We review the molecular basis of three related basic helix–loop–helix (bHLH) genes ( Neurog1 , Neurod1 , and Atoh1 ) and upstream regulators Eya1/Six1 , Sox2 , Pax2 , Gata3 , Fgfr2b , Foxg1 , and Lmx1a/b during the development of spiral ganglia, cochlear nuclei, and cochlea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 134 publications
(297 reference statements)
0
9
0
Order By: Relevance
“…neurod1, egr2b, tfap2a, and phox2a have been shown to be related to CNS development (Tahayato et al, 2003;Uehara et al, 2007;Zhang et al, 2017;Kousa et al, 2019;10.3389/fnins.2022.960149 FIGURE 4 The effect of loss of rnf2 on the specification of neural crest cells. Song et al, 2020;Elliott et al, 2021). The results showed that the expression of tfap2a was slightly reduced in rnf2 −/− embryos compared to controls, especially in the middle and hindbrain regions (Figure 6A).…”
Section: Rnf2 Loss Of Function Affects Central Nervous System Develop...mentioning
confidence: 83%
See 1 more Smart Citation
“…neurod1, egr2b, tfap2a, and phox2a have been shown to be related to CNS development (Tahayato et al, 2003;Uehara et al, 2007;Zhang et al, 2017;Kousa et al, 2019;10.3389/fnins.2022.960149 FIGURE 4 The effect of loss of rnf2 on the specification of neural crest cells. Song et al, 2020;Elliott et al, 2021). The results showed that the expression of tfap2a was slightly reduced in rnf2 −/− embryos compared to controls, especially in the middle and hindbrain regions (Figure 6A).…”
Section: Rnf2 Loss Of Function Affects Central Nervous System Develop...mentioning
confidence: 83%
“…To this end, we performed in situ hybridization against neurod1 , egr2b , tfap2a , and phox2a in 48 hpf control and rnf2 mutant embryos ( Figure 6 ). neurod1 , egr2b , tfap2a , and phox2a have been shown to be related to CNS development ( Tahayato et al, 2003 ; Uehara et al, 2007 ; Zhang et al, 2017 ; Kousa et al, 2019 ; Song et al, 2020 ; Elliott et al, 2021 ). The results showed that the expression of tfap2a was slightly reduced in rnf2 –/– embryos compared to controls, especially in the middle and hindbrain regions ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…Neurod1 negatively regulates Atoh1 expression during cerebellum, and gut proliferation and manipulating Neurod1 expression that may help to counteract Medulloblastoma [ 67 , 68 , 69 , 70 ]. Atoh1 shows a much higher level of expression in the auditory nuclei and counteracts with Neurod1 , indicating a differential regulation of expression in auditory nuclei [ 71 ].…”
Section: Early Ear Placodal Development: From Unspecified Cells To Ne...mentioning
confidence: 99%
“…A good example of this is the dA1 (Atoh1 +) domain in rhombomere 1 (upper rhombic lip). This domain generates: in addition to the parabrachial/Kölliker-Fuse complex, all excitatory deep cerebellar neurons, all cerebellar granule cell progenitors, as well as all cerebellar and cochlear unipolar brush cells ( Englund et al, 2006 ; Fink et al, 2006 ; Ray and Dymecki, 2009 ; Hernandez-Miranda et al, 2017a ; van der Heijden and Zoghbi, 2018 , 2020 ; Elliott et al, 2021 ; Lowenstein et al, 2021 , 2022 ; Fritzsch et al, 2022 ). How these progenitors generate such a vast array of neuron types is currently being investigated and appears to depend on the temporal expression of transcription factors that act as selector genes.…”
Section: Cell Lineages Contributing To Respiratory and Non-respirator...mentioning
confidence: 99%